VHF adaptive antenna using a rear defogger - Abdullah, Noorsaliza (2012)
This thesis presented the design of an adaptive bearnforming antenna using a rear defogger. The main purpose of this project is to develop the vehicular adaptive antenna for VHF band, which does not require the installation space, does not spoil the industrial design, has low cost and low power consumption. In land communication, there is no clear line of sight between transmitter and receiver. The transmitted signal might be reflected, refracted because of the building or terrain. The receiver might receive a delayed, or reflected signal instead of the original signal. Adaptive antenna is the best candidate to mitigate the multipath fading effects. However, for VHF band, conventional adaptive antenna has a drawback of a large aperture size. Therefore, in this paper a rear defogger is proposed as an aperture to overcome the size problem of using a conventional adaptive antenna. A rear defogger of a vehicle can be used as an aperture, '7-3 and in order to make it compatible with ESPAR antenna, several ports have been 1 1, provided. One port is used as an active port or output port, while other ports are connected to the variable reactor. Downhill simplex method is used as an algorithm to form the adaptive beam for the proposed antenna. This algorithm is maximized the correlation coefficients. Simplex method has been chosen because it has several advantages. Simplex method has a fast convergence time, robust beamforming, and it can be used for multi-dimensional optimization. There are several steps in simplex method for optimization; reflection, expansion, contraction, and multiple contractions. IE3D software is used to model the defogger with the car and from the IE3D results it shows that the defogger can be used as an adaptive antenna because it has low voltage standing wave ratio (VSWR) to make it operate as an antenna, low spatial cross correlation (SCC) for better diversity and has high coupling between port (CBP) for better capability of beamforming. In the analysis, the VSWR is lower than 3, SCC is lower than 0.5, and the CBP is between -6 dB to -10 dB. For numerical simulation, MATLAB is used to make a program for simplex method. From the simulation results, it shows that almost 80 % of the signals have signal to interference noise ratio (SINR) greater than 20 dB. Besides that, null is performed for incoming interference and remained high gain for the desired signal. A Rear defogger is made from heating wire, therefore it is necessary to confirm the effects of the resistivity to the antenna's performance. The effects of the resistivity has been confirm through IE3D simulator and MATLAB programming by comparing it to the copper wire. From IE3D simulator, comparison has been made for VSWR, SCC, and CBP for both resistive and copper wire. The results show that the values of VSWR, SCC, and CBP for copper and resistive wires are nearly same. A statistical analysis has been carried out for copper and resistive wire, and the analysis show that the performance of the resistive wire is slightly decrease compared to copper wire. However, the different is very small, plus the resistive wire has more than 80% of the signal has SINR greater than 20 dB. The beam pattern is controlled by a varactor circuit. The varactor circuit is connected to the three passive elements. The reactance range is limited from - j300Q to j3000 in the simulation, consider manufacturing. It is difficult to manufacture a large range of reactance. The reactance value is different for each incoming DOAs. Measurement has been conducted in anechoic chambers for adaptive beamforming. It shows that after perform beamfonning, null is performed for incoming interference, improved VSWR, BER and SINR over the bandwidth. The proposed antenna has a fast convergence times, the convergence time is less than 50 ms and the iteration number is less than 70. Measurement in Rayleigh fading environment also been conducted, it shows that by applying the beamforming the BER is improved. The experiment was conducted for 473 ' * ' , xi MHz and 900 MHz for horizontal (co-polarization) and vertical (cross-polarization). For both co-polarization and cross-polarization, BER show an improvement